Management of natal tooth of a 2 months old infant: a case report - Sharma, Vipul; Saxena, Nivedita; Nigam, Anant Gopal; Singh, Vritika (International Journal of Contemporary Pediatrics, 2024)
Natal and neonatal teeth are the type of supernumerary tooth which have various myths and superstitions associated with it. Natal teeth are the teeth which appear at the time of the birth whereas neonatal teeth appear within one month of life. Presence of natal teeth often risks the aspiration of teeth by infant and the mother also has difficulty in breast feeding and comes with the complaint of the same. The present case report of 2-month-old infant describes the management of natal teeth present in mandibular arch with mobility. After the consent of parents, the extraction of the shell-like tooth was done immediately and hemostasis was achieved. The follow up was carried out after 1 week to examine the normal healing of extraction site.